EFEK EKSTRAK BUAH TOMAT (Licopersicum pyriforme) TERHADAP EKSP KOLAGEN TIPE 1, MMP-1 DAN MMP-3 PADA PENUAAN KULIT - Wahyono, Poncojari (Jurnal Kedokteran Brawijaya, 2008)
ABSTRACT Many  theory  and  research  was  trying  to  explain  the  aging  process.  Free  radical  theory  explained  that  allnormal metabolism process in the body can produce free radical.These free radical can destroy the skin cell,and  than  the  skin  will  start  the  aging  process.  The  tomato  extract  has  antioxidant  such  as  lycopene,  β-carotene  and  vitamin  C.  These  antioxidant  will  prevent  the  activity  of  free  radical,  so  that  skin  cell  will  notdamage.  The  aims  of  this  research  were  to  study  effect  of  tomato  extract  juice  in  preventing  skin  aging  onwistar rats. Total of 25 rats were divided into 5 groups, consisted of 5 rats each. Group one was control groupD-0) rats were four months old, and the group two control of group rats were taken care of 4 months old until7  months  old  (D-1),  the  other  group  which  were  under  treatment  classified  into  3  groups.  Group  three  wereed 7 g/kg/day/ body weight of tomato fruit extract, then taken care of 4 months old until 7 months old (D-2),group four were fed 11 g/kg/day/ body weight of tomato extract fruit, then taken care of 4 months old until 7months old (D-3) and group five were fed 15 g/kg/day/ body weigh of tomato fruit extract, then taken care of 4months  old  until  7  months  old  (D-4).